2020
DOI: 10.38009/ekimad.694300
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye'de Yenilenebilir Enerji Tüketimini Etkileyen Faktörlerinin MARS Metodolojisi İle Belirlenmesi

Abstract: The aim of this study is to determine the factors affecting the renewable energy consumption in Turkey. In this context, firstly, similar studies in the literature have been examined. As a result of the investigation, 11 different variables have been identified that may affect the use of renewable energy. Annual data of the mentioned variables in the period of 1990-2018 are taken into consideration. On the other hand, MARS method is used in the analysis process of the study. As a result, it has been determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In addition, the results revealed absence of link between renewable energy consumption and economic growth and between renewable energy consumption and trade in short run. Yüksel and Ubay (2020) aimed to find the leading indicators of renewable energy consumption. It is identified that increase in natural gas prices leads to higher consumption of renewable energy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, the results revealed absence of link between renewable energy consumption and economic growth and between renewable energy consumption and trade in short run. Yüksel and Ubay (2020) aimed to find the leading indicators of renewable energy consumption. It is identified that increase in natural gas prices leads to higher consumption of renewable energy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Kahia et al (2016), there is a short-term negative association between RE and non-RE use, confirming the bidirectional causality that demonstrates the substitutability of the two energy types. Consumption of fossil-based sources has been identified as a key component in the transition from non-renewable to RE sources (Yuksel and Ubay, 2020). Another study by Dong et al (2017) claims that there is a bidirectional relationship between natural gas use and RE utilization in the long term.…”
Section: Methodsmentioning
confidence: 99%